C-Phycocyanin as a tumour-associated macrophage-targeted photosensitiser and a vehicle of phthalocyanine for enhanced photodynamic therapy. Issue 29 (28th March 2017) - Wan, Dong-Hua; Zheng, Bi-Yuan; Ke, Mei-Rong; Duan, Ji-Ying; Zheng, Yun-Quan; Yeh, Chih-Kuang; Huang, Jian-Dong
Abstract : C-Phycocyanin was first reported as a tumour-associated macrophage targeted photosensitiser and a vehicle of zinc phthalocyanine for enhanced photodynamic therapy. Abstract : C-Phycocyanin (CPC) as a tumour-associated macrophage (TAM)-targeted photosensitiser has been first proved, and used as a vehicle of zinc phthalocyanine (ZnPc) to fabricate a ZnPc–CPC conjugate, which exhibits an efficient in vitro photodynamic activity, and selectively accumulates in tumour sites probably due to the affinity to TAM.